Investigation and Analysis of the Acceptance of the License Plate–Based Restriction Policy: A Case Study in Hangzhou, China - Yexing Yin; Gang Yu; Rongchuan Lin; Sheng Jin; Cheng Xu (Journal of Advanced Transportation)
In order to better understand the factors that affect Hangzhou residents’ acceptance of the license plate–based restriction (LPR) policy, new factors such as fairness, family life cycle factors, and preacceptance of alternative measures were added to explore new interactions between different factors. A questionnaire survey was completed among 958 residents of Hangzhou City, and a partial least squares structural equation model (PLS-SEM) was established to analyze the factors that affect the acceptance of the LPR policy. An analysis of socioeconomic attributes is conducted to explore the impact of education, age, and family life cycle factors on the acceptance of the LPR policy. The results indicate that perceived cost-effectiveness, social norms, policy cognition, fairness, important goals, and preacceptance of alternative measures have significant direct effects on the postacceptance of the LPR policy, while fairness and important goals have indirect effects through social norms. Regarding postacceptance, perceived effectiveness can only indirectly affect postacceptance of the LPR policy through policy cognition and perceived cost-effectiveness. Responsibility attribution can only indirectly affect postacceptance through important goals. As the education level and age increase, residents’ acceptance of the LPR policy will decrease; young families without children and families with minor children have lower acceptance of the LPR policy than families with all adult members and elder families without children.